MILITARY AND POLITICAL TOURISM ATTRACTIONS IN THE CITY OF GDAŃSK - Paul PANTEA; Geraldine ŞOTAN-PETYKE; Daria-Maria CRIŞAN; Jan A. WENDT (Revista Română de Geografie Politică)
Military tourism is an atypical and recent form of tourism that is not sufficiently researched in the city of Gdańsk, northern Poland. However, the interest surrounding this phenomenon has been growing, which indicates the possibility of further development of military and political tourism in the area. The aim of this research is to present the major touristic attractions and to analyse the tourist traffic that play an important role in the overall development of military and political tourism in the city. The study is focusing on the following attractions: the Museum of the Second World War, Westerplatte and the European Solidarity Centre, as well as analysing the tourist flow.